Effects of donor smoking history on early post-transplant lung function measured by oscillometry - Belousova, Natalia; Cheng, Albert; Matelski, John; Vasileva, Anastasiia; Wu, Joyce K. Y.; Ghany, Rasheed; Martinu, Tereza; Ryan, Clodagh M.; Chow, Chung-Wai (Frontiers in Medicine, 2024)
Prior studies assessing outcomes of lung transplants from cigarette-smoking donors found mixed results. Oscillometry, a non-invasive test of respiratory impedance, detects changes in lung function of smokers prior to diagnosis of COPD, and identifies spirometrically silent episodes of rejection post-transplant. We hypothesise that oscillometry could identify abnormalities in recipients of smoking donor lungs and discriminate from non-smoking donors. This prospective single-center cohort study analysed 233 double-lung recipients. Oscillometry was performed alongside routine conventuional pulmonary function tests (PFT) post-transplant. Multivariable regression models were constructed to compare oscillometry and conventional PFT parameters between recipients of lungs from smoking vs non-smoking donors.The analysis included 109 patients who received lungs from non-smokers and 124 from smokers. Multivariable analysis identified significant differences between recipients of smoking and non-smoking lungs in the oscillometric measurements R5-19, X5, AX, R5z and X5z, but no differences in %predicted FEV1, FEV1/FVC, %predicted TLC or %predicted DLCO. An analysis of the smoking group also demonstrated associations between increasing smoke exposure, quantified in pack years, and all the oscillometry parameters, but not the conventional PFT parameters.An interaction was identified between donor-recipient sex match and the effect of smoking. The association between donor smoking and oscillometry outcomes was significant predominantly in the female donor/female recipient group.Oscillometry identifies post-transplant abnormalities in the lungs of smoking donors, which are not apparent with conventional PFT. An interaction between sex match and donor smoking warrants further investigation.